LEGAL DIMENSIONS OF THE RESPONSIBILITY OF COMPANIES THAT VIOLATE ECONOMIC SANCTIONS FROM THE PERSPECTIVE OF INTERNATIONAL LAW (CAHIERS MAGELLANES-NS, 2024)
Sanctions are a weapon in the hands of some countries that are used against other countries, and this has led some companies to circumvent sanctions by being considered violators and the burden of civil liability and sometimes Criminal responsibility should be on them. The subject of contracts and economic activities of companies in the period when economic sanctions prevail, assuming the conclusion of the contract, is void and it is not possible to remove the responsibility by resorting to civil and criminal liability factors such as emergency, coercion, force majeure, etc. For example, joint stock, manufacturing, industrial, etc. companies cannot enter into a contract because the country's economic situation in a state of emergency requires a specific commodity. In this regard, no executive guarantee is provided in domestic regulations, but in this regard, special regulations can be cited in international regulations, although in the author's opinion, force majeure conditions, if they have all the conditions, are among the factors that relieve responsibility. Consequently, in the present article, we will discuss the legal aspects of the liability of companies violating economic sanctions from the perspective of international law through the library method and the study of existing domestic and international laws and regulations.